1999
DOI: 10.1007/bf03173114
|View full text |Cite
|
Sign up to set email alerts
|

Formal reasoning performance of higher secondary school students: Theoretical and educational implications

Abstract: The study investigat ed the structure and development offormal thought among tenth-, eleve nth-, and twelfth-grade students . The subjects of the study were the total numbers of students attending the science. the economic. and the other sections of two higher secondary schools. Students ' performance on a standardized Test of Logical Thinking (TOLT) was used as a measure of their cognitive abilities related to control ofvariables. proportional. probabilistic. correlational, and combinatorial reasoning. Studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This is a significant problem for a large percentage of students who enroll in chemistry courses. Studies of the reasoning skills of students entering college consistently show that only about 25% are well equipped with the skills needed to solve conceptual problems (10)(11)(12). Our own researchin-progress data show that only 8% of high school juniors and 22% of college freshmen who are beginning a chemistry course enter with sufficient reasoning skills to have the potential to be successful conceptual problem solvers.…”
mentioning
confidence: 72%
“…This is a significant problem for a large percentage of students who enroll in chemistry courses. Studies of the reasoning skills of students entering college consistently show that only about 25% are well equipped with the skills needed to solve conceptual problems (10)(11)(12). Our own researchin-progress data show that only 8% of high school juniors and 22% of college freshmen who are beginning a chemistry course enter with sufficient reasoning skills to have the potential to be successful conceptual problem solvers.…”
mentioning
confidence: 72%
“…Studies revealed several ways to measure this skill. The logical thinking test is an instrument that measures formal reasoning and cognitive abilities in a person which consists of five modes, namely, controlling variable, proportional reasoning, combinatorial reasoning, probabilistic reasoning, and correlational reasoning in coordinance with Piaget's developmental theory (Pogozhina, 2016;Tobin & Capie, 1981;Valanides, 1999). The most common test called the test of logical thinking (TOLT) developed by Tobin & Capie (1981).…”
Section: Theoretical Frameworkmentioning
confidence: 99%